BOTHO/UBUNTU: THE HEART OF AFRICAN ETHICS - Dolamo, Ramathate Tseka Hosea (Scriptura, 2013)
The tenets of botho/ubuntu analysed in this article demonstrate the interplay between individuals and their respective communities. A thorough but not exhaustive definition and description of ubuntu are given, indicating its indispensable elements, which are derived from African culture and religion. This article indicates that culture and religion are not static entities, that in this postmodernist and globalising world ubuntu could be enriched by taking cognisance of the values and principles of other cultures and religions.